IDENTIFIKASI PENYALAHGUNAAN PERUNTUKAN RUANG TERBUKA HIJAU PADA PEMBANGUNAN KAWASAN KULINER DI PLUIT JAKARTA UTARA - Almira Muthi Faliha; Annisa Aulia Suwandi; Dewi M Z S Pertiwi; Dedi Hantono (Universitas Batam, 2021)
The increasing demand for space, especially for settlements and built-up land, has an impact on the declining environmental quality of the area. The Spatial Plan that has been made is not able to prevent land conversion in urban areas so that the existence of Green Open Space (RTH) is increasingly threatened and the city is increasingly uncomfortable for activities, especially for joint activities. This study will discuss the